Kajian Penggunaan Tween80™ Pada Pelbagai Konsentrasi Nira Nipah Kental Dalam Proses Fermentasi Bioetanol - Rezita Azizah; Fajar Restuhadi; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The aimed of the research was to obtain the best combination treatment between early sugar concentration and Tween80 concentration as surfactant and nutrition for Saccaromyces cerevisiae to produce ethanol on very high gravity fermentation from Nypa sap. The exploration research used two factor treatments with two replications. The treatments consist of early sugar concentration N1 (20%), N2 (25%), N3 (30%) and Tween80 concentration T0 (0%), T1 (0,2%), T2 (0,4%), T3 (0,6%). Observation was conducted every 24 hours i.e sugar concentration, ethanol concentration, amount of cell, and pH. Data obtained were analyzed by descriptive method. The best combination treatment was T1N3 (Tween80 0,2% and N 30%) which produced ethanol 16,20%. Keywords: Nypa sap, Tween80, Bioethanol, Very High Gravity Fermentation